Positive Influence of Probiotics on the Mental Health Status of College Students: A Review - Guiao, Renee Alexis S.; Adviento, Dancel A.; Angeles, Trisha Gaile C.; Belandres, Jade Anne V.; Guzman, Nicole Anne S. De; Librea, Gwyneth A.; Rullan, Jochelle Anne V.; Hagosojos, Bernardino M. (Asian Journal of Biological and Life Sciences)
Evidence of a growing population with mental health issues is prevalent, notably in college students. Due to this, many researchers conducted a study on how to enhance the well-being of an individual. Literature explained the connection between the brain and gut axis and found out that consuming a significant amount of probiotics positively impacts an individual’s mental state. Further study about this mechanism can imply more knowledge about the microbiome-gut-brain axis and aid in additional supplemental control associated with psychiatric health. This paper aims to determine the communication process between the gut and brain signaling and determine how prebiotics and probiotics or the so-called “psychobiotics” influence college students’ psychological well-being. A total of 2,563 works of literature were gathered from credible sites, including PubMed and ScienceDirect, published between 2015 to present year. The literature studies expound on different mental health problems of college students and show the correlation of probiotic consumption to an individual’s overall mental health impact. Throughout the extensive analysis of the literature gathered, this study suggests that probiotics can potentially increase the mental well-being of an individual. There is a number of evidence and data that support probiotics as a supplement that can help particularly in reducing signs of depression, anxiety, stress, and other mental health problems.
Keywords: Anxiety; College; Gut-brain-axis; Mental Health; Probiotics; Stress